2012
DOI: 10.1042/an20120008
|View full text |Cite
|
Sign up to set email alerts
|

IL-1RI (Interleukin-1 Receptor Type I) Signalling is Essential for Host Defence and Hemichannel Activity During Acute Central Nervous System Bacterial Infection

Abstract: Staphylococcus aureus is a common aetiological agent of bacterial brain abscesses. We have previously established that a considerable IL-1 (interleukin-1) response is elicited immediately following S. aureus infection, where the cytokine can exert pleiotropic effects on glial activation and blood–brain barrier permeability. To assess the combined actions of IL-1α and IL-1β during CNS (central nervous system) infection, host defence responses were evaluated in IL-1RI (IL-1 rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 50 publications
2
17
0
Order By: Relevance
“…Prior work from our laboratory demonstrated that IL‐1RI KO mice succumb to CNS S. aureus infection within the first 24 h following bacterial exposure (Xiong et al . ); therefore, we predicted that similar results would be observed for both NLRP3 and ASC KO animals, since this inflammasome platform has the largest range of molecular triggers leading to IL‐1β processing and release. Unexpectedly, ASC, but not NLRP3 KO mice were exquisitely sensitive to CNS S. aureus infection.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…Prior work from our laboratory demonstrated that IL‐1RI KO mice succumb to CNS S. aureus infection within the first 24 h following bacterial exposure (Xiong et al . ); therefore, we predicted that similar results would be observed for both NLRP3 and ASC KO animals, since this inflammasome platform has the largest range of molecular triggers leading to IL‐1β processing and release. Unexpectedly, ASC, but not NLRP3 KO mice were exquisitely sensitive to CNS S. aureus infection.…”
Section: Discussionsupporting
confidence: 59%
“…; Xiong et al . ). However, we did not detect any significant differences in peripheral leukocyte infiltrates or bacterial burdens between WT and ASC or AIM2 KO mice in this study, which may result from the combined actions of IL‐1β and IL‐1α loss in IL‐1RI KO animals in our previous report (Xiong et al .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…As such, ATP that is released after CNS damage may not only act as an excitotoxic molecule, but it can also significantly contribute to inflammatory responses, thereby exacerbating the release of inflammatory cytokines. Proinflammatory cytokines TNF-a and IL1-b can furthermore reduce astroglial GJIC, while astroglial and microglial HCs and Panx1 channels are reported to open [45,52,336,[343][344][345][346]. It has been demonstrated in several scenarios, such as inflammatory conditions, ischemia and exposure to amyloid b, that a combined action of astrocytic Cx43 HCs, and microglial Cx43 HCs and Panx1 channels contributes to the reciprocal astrocyte-microglial communication and eventually to neuronal dysfunction [57,67,347,348].…”
Section: Contribution Of Astroglial Connexins To Vasomotor Control Anmentioning
confidence: 99%